Estudo comparativo in vitro dos níveis radiográficos de cinza de biomateriais utilizando duas modalidades de imagem digital - Nobrega, Newton Fernando Sobreira [UNIFESP] (2009)
Purpose: To compare direct and indirect methods using the Digora for Windows System and the Adobe Photoshop CS2 System. Methods: Samples were made of dental materials, using a matrix of metallic aluminum structure composed of two blocks coupled by a precision connection. The samples were disposed on a radiographic film and on a protected phosphor plate to be radiographed using the indirect and direct methods. The radiographic images were analyzed by the Digora for Windows system and the Adobe Photoshop system which have 256 shades of gray, followed by the delimitation of the standard area for measuring of the shades of gray. Results: The distribution of the shades of gray, analyzed by the direct and indirect methods, suggested that the greater the distance, the longer the time of exposure. Conclusion: The indirect method was a feasible alternative in the evaluation of radiographical shades of gray in dental materials since it presents significant reproductiveness in 0,2s to 0,5s exposure.